1996
DOI: 10.1002/(sici)1097-0142(19960115)77:2<223::aid-cncr1>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Salivary duct carcinoma: Clinicopathologic and immunohistochemical review of 26 cases

Abstract: The prognosis for SDC is dismal, and clinically useful prognostic factors were not found. Our results do not confirm hormonal concordance between SDC and breast carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
194
1
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(222 citation statements)
references
References 29 publications
26
194
1
1
Order By: Relevance
“…LG-SDC and conventional SDC are composed of neoplastic cells with ductal phenotype and varying degree of apocrine differentiation and AR expression [1,6,14,31,41] but exhibit significant clinicopathologic differences including the expression of S100 protein, with 84 % of LG-SDCs positive for S100 protein. In contrast, the data regarding S100 protein expression in conventional SDC is more controversial with Lewis et al [30] reporting expression in only 4 % while Brandwein et al [42] reported reaction in 100 % of cases. The presence of at least focal LG-SDC has not been described in any study of conventional SDC.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…LG-SDC and conventional SDC are composed of neoplastic cells with ductal phenotype and varying degree of apocrine differentiation and AR expression [1,6,14,31,41] but exhibit significant clinicopathologic differences including the expression of S100 protein, with 84 % of LG-SDCs positive for S100 protein. In contrast, the data regarding S100 protein expression in conventional SDC is more controversial with Lewis et al [30] reporting expression in only 4 % while Brandwein et al [42] reported reaction in 100 % of cases. The presence of at least focal LG-SDC has not been described in any study of conventional SDC.…”
Section: Discussionmentioning
confidence: 97%
“…It occurs mostly in elderly patients, has a male predilection and usually present as a rapidly growing tumor in the parotid gland. Unlike LG-SDC, it is notorious for early distant metastases and high mortality [30]. SDC resembles high grade ductal carcinoma of breast, with both intraductal and widely invasive components.…”
Section: Conventional Salivary Duct Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…SDC is a distinctive but relatively common high grade adenocarcinoma arising from the excretory ductal epithelium of the major salivary glands, especially the parotid gland [8-10]. Clinically, these tumors are characterized by aggressive (i.e., infiltrative and destructive) behavior with local recurrence, early and distant metastasis, invasion of the facial nerve, and/or significant mortality [8-11].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, these tumors are characterized by aggressive (i.e., infiltrative and destructive) behavior with local recurrence, early and distant metastasis, invasion of the facial nerve, and/or significant mortality [8-11]. Histopathologically, SDCs have a striking resemblance to ductal carcinoma of the breast, exhibiting intraductal and infiltrating components [8,10,11]. In addition, very intriguingly, they should show a broader clinicopathological spectrum and many cases of them may develop within PA as a result of malignant transformation of ductal epithelial cells [9,12].…”
Section: Introductionmentioning
confidence: 99%